Child maltreatment prevention: a systematic review of reviews - Christopher Mikton; Alexander Butchart (The World Health Organization, 2009)
OBJECTIVE: To synthesize recent evidence from systematic and comprehensive reviews on the effectiveness of universal and selective child maltreatment prevention interventions, evaluate the methodological quality of the reviews and outcome evaluation studies they are based on, and map the geographical distribution of the evidence. METHODS: A systematic review of reviews was conducted. The quality of the systematic reviews was evaluated with a tool for the assessment of multiple systematic reviews (AMSTAR), and the quality of the outcome evaluations was assessed using indicators of internal validity and of the construct validity of outcome measures. FINDINGS: The review focused on seven main types of interventions: home visiting, parent education, child sex abuse prevention, abusive head trauma prevention, multi-component interventions, media-based interventions, and support and mutual aid groups. Four of the seven - home-visiting, parent education, abusive head trauma prevention and multi-component interventions - show promise in preventing actual child maltreatment. Three of them - home visiting, parent education and child sexual abuse prevention - appear effective in reducing risk factors for child maltreatment, although these conclusions are tentative due to the methodological shortcomings of the reviews and outcome evaluation studies they draw on. An analysis of the geographical distribution of the evidence shows that outcome evaluations of child maltreatment prevention interventions are exceedingly rare in low- and middle-income countries and make up only 0.6% of the total evidence base. CONCLUSION: Evidence for the effectiveness of four of the seven main types of interventions for preventing child maltreatment is promising, although it is weakened by methodological problems and paucity of outcome evaluations from low- and middle-income countries.